2017
DOI: 10.1096/fj.201600735r
|View full text |Cite
|
Sign up to set email alerts
|

LPA 1 receptor–mediated thromboxane A 2 release is responsible for lysophosphatidic acid‐induced vascular smooth muscle contraction

Abstract: Lysophosphatidic acid (LPA) has been recognized recently as an endothelium-dependent vasodilator, but several lines of evidence indicate that it may also stimulate vascular smooth muscle cells (VSMCs), thereby contributing to vasoregulation and remodeling. In the present study, mRNA expression of all 6 LPA receptor genes was detected in murine aortic VSMCs, with the highest levels of LPA, LPA, LPA, and LPA In endothelium-denuded thoracic aorta (TA) and abdominal aorta (AA) segments, 1-oleoyl-LPA and the LPA ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Thoracic aortae were cut into segments and were placed on stainless steel vessel holders (200 μm in diameter) in a myograph (610M multiwire myograph system, Danish Myo Technology A/S). Experimental protocol was described previously (17,71). Mice used for the experiments were caged with blinded identity and in random order.…”
Section: Methodsmentioning
confidence: 99%
“…Thoracic aortae were cut into segments and were placed on stainless steel vessel holders (200 μm in diameter) in a myograph (610M multiwire myograph system, Danish Myo Technology A/S). Experimental protocol was described previously (17,71). Mice used for the experiments were caged with blinded identity and in random order.…”
Section: Methodsmentioning
confidence: 99%
“…Studies performed in mice and human revealed that smooth muscle cells (Panchatcharam et al 2008, Subramanian et al 2010, Dancs et al 2017, endothelial cells (Zhou et al 2011) and platelets (Haserück et al 2004, Pamuklar et al 2008 present in the vasculature respond to LPA (Cheng et al 2009, Morris et al 2009a. These interactions are involved in the regulation of blood vessel development and contribute to vascular biology and pathology (Mueller et al 2015).…”
Section: Lpa As a Vascular Mediatormentioning
confidence: 99%
“…Lack of pronounced expression of LPA receptors, in particular LPA 1 receptor, in arteriolar tunica intima was an unexpected finding. Prior findings in animal models and endothelial cell cultures show majority of LPA effects being mediated through LPA 1 receptor (Gobeil et al ., ; Brault et al ., ; Cui, ; Ruisanchez et al ., ; Dancs et al ., ). Additionally, we and others observe strong protein and RNA expression in cultured endothelial cells (Lin et al ., ; Ptaszynska et al ., ; Ren et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Faint expression of LPA 3 receptor protein was also detected in HUVECs. Absence or minimal expression of LPA 3 has been observed in endothelial (Lee et al ., ; Lin et al ., ; Ruisanchez et al ., ) and smooth muscle (Dancs et al ., ) cells from animal models or cultured vascular human cell lines. We confirmed previously published data using HUVEC and HMVECs.…”
Section: Discussionmentioning
confidence: 99%